Analysis of River Water Quality Based on Pollution Index Water Quality Status, Lombok District, NTB - Supardiono Supardiono; Gito Hadiprayitno; Jono Irawan; Lalu Adi Gunawan (Postgraduate, University of Mataram, 2023)
Leneng River is one of the rivers in Praya City, Central Lombok Regency, which receives domestic, agricultural, and household industrial waste. Various community activities along the banks of the Leneng River have affected river water quality. Some communities on the banks of the Leneng River, from upstream to downstream, still use river water for their daily needs. This study aims to 1) analyze the water quality of the Leneng River in terms of environmental parameters (Physical, chemical, and biological) and 2) Determine the level of pollution of the Leneng River water using the Pollution Index (IP) method. River water quality measurements were carried out at 3 (three) sample points. Parameters measured and observed were physical parameters, namely Total Solid Suspend (TSS); chemical parameters, namely pH, Total Phosphate (T.PO4), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), and biological parameters namely Total coliform and Fecal Coliform. This type of research is survey research with a quantitative descriptive approach. The results showed that the TSS value at sample point 1 (upstream) exceeded the required quality standard; the highest TSS concentration value was 54 mg/L, and the lowest at sample point 2 (middle section) was 2.50 mg/L. Value parameter concentration pH 7.7-8.7, T.PO4 value 0.05 mg/L-0.29 mg/L, BOD value 0.17-0.42 mg/L, COD concentration value 8 mg/L -9mg/L, and DO value of 6.07 mg/L-7.57 mg/L, this shows that the concentration for chemical parameters still meets the class I water quality standards according to PP 22 of 2021, while the total coliform parameter value and Facel coliform have exceeded class I water quality standards. The total coliform concentration value is 10,000 - 20,000 MPN/100 mL, and the Fecal coliform value is 600 MPN/100 mL – 2,500 MPN/100 mL, while based on the Pollution Index (IP) quality status water in the upstream with a value of 2.84, the middle part of 1.97, and the downstream part of 2.84, this shows a decrease in water quality from upstream to downstream of the river, with a level of pollution in the lightly polluted category.